Analysis of internal factors of green supply chain management: An interpretive structural modeling approach - Arka Chakraborty (17808296) (2023)
The industrial revolution in the world brings environmental concern in industrial and production sector which puts more focuses on the green or sustainable supply chain practice. Green supply chain management is focused on ensuring sustainable production and customer order fulfillment through a series of activities. In this study internal factors of green supply chain management practice are analyzed, and theoretical model is developed according to the driving power and dependence power of the factor. This study is performed in interpretive structural modelling (ISM) approach where industry experts were consulted to include their industry experience in the evaluation process. The study has identified eight factors which can be controlled internally within the organization. Among these eight factors, commitment from the top management is the most crucial factor for its’ highest driving power. The reverse logistic process stands on the next, and material storing and management on the upper level. Other Information Published in: Cleaner Logistics and Supply Chain License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.clscn.2023.100099